Is zero the best price? Optimal pricing of mobile applications - Christoph Buck; Julia Graf (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2015)
[Introduction ...] This leads us to our major research question: How to optimally set prices of mobile applications depending on their utility-classification? Each of the following chapters sequentially contributes to the answer of this question. Chapter 2 focuses on the managerial relevance of pricing and the specific characteristics of mobile applications. In chapter 3, we develop a model for mobile application pricing and derive advises for profit-maximizing mobile application pricing. The article closes with a discussion and conclusion in chapter 4.
urn:nbn:de:bvb:703-epub-1896-6
Keywords: 650; Optimal Pricing; Mobile Applications; Apps; Price